Neuroprotective effect of silymarin-loaded nanoliposomes against monosodium glutamate-induced cerebellar motor deficit and Purkinje cell damage in experimental rats via PI3K/AKT pathway activation - Medhat Taha; Medhat Taha; Ahmed Alzahrani; Omer Abdelbagi; Rehab M. Bagadood; Naeem F. Qusty; Rami Obaid; Mohammad El-Nablaway; Mohammad El-Nablaway; Tourki A. S. Baokbah (Frontiers in Molecular Biosciences)
Background and aimThis study investigated the ameliorative effect of Silymarin-nanoliposome (SLNPs) against monosodium glutamate (MSG)-induced cerebellar toxicity, illuminating its impact on motor coordination.MethodsForty male Wistar albino rats were divided into four groups. Group I (control group): rats received 2 mL of 0.9% NaCl solution; Group II (SLNPs group): rats received SLNPs with a dose of 500 μg/kg bw orally; Group III (MSG group): rats received 3.5 mg/kg bw of MSG intraperitoneally; and Group IV: rats received combined treatment of MSG + SLNPs for ten consecutive days.ResultsMSG-induced cerebellar motor incoordination is represented by increased falls in rats and decreased tow latency spent on the rotarod test. Moreover, MSG altered cerebellar histological structure and significantly (p < 0.05) decreased antioxidant system activity and protein levels of phosphorylated phosphoinositide 3-kinases (p-PI3K), phosphorylated protein kinase B (p-AKT), and brain-derived neurotrophic factor (BDNF). Additionally, there is a decrease in the immunoexpression of nuclear factor erythroid 2-related factor 2 (Nrf2) and gene expression of heme oxygenase-1 (HO-1), tropomyosin receptor kinase B (TrkB), and anti-apoptotic B-cell lymphoma-2 (Bcl-2), alongside an increase in the sera and protein levels of proinflammatory cytokines tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), interleukin-1 beta (IL-1β), immunoexpression of glial fibrillary acidic protein (GFAP), nuclear factor kabba beta (NF-κB), caspase-3, and gene expression of proapoptotic Bax. However, SLNPs prevented MSG-induced cerebellar toxicity, improving motor coordination and morphological structure by enhancing antioxidant, anti-inflammatory, and anti-apoptotic activity by stimulating the PI3K/AKT pathway.ConclusionThe current study indicated that SLNP administration protects against MSG-induced cerebellar damage, preventing cerebellar oxidative stress, inflammation, and apoptosis, opening the door to examining its clinical use in preventing MSG-induced cerebellar motor incoordination.